CagA gene EPIYA motif genetic characterization from Colombian Helicobacter pylori isolates: Standardization of a molecular test for rapid clinical laboratory detection (2020)
The aim of this work was to determine current cagA gene EPIYA motifs present in Colombian Helicobacter pylori isolates using a fast and reliable molecular test. DNA from eightyfive Helicobacter pylori-cagA positive strains were analyzed. Strains were obtained from patients diagnosed with functional dyspepsia at Cl? nica Fundadores in Bogota . The 3' region of the cagA gene was amplified through conventional Polymerase Chain Reaction (PCR). Obtained amplicons were sequenced using the Sanger method and analyzed with bioinformatics tools. Additionally, a significant Spearman correlation coefficient was determined between the patients' age and the number of EPIYA-C repeats; with p values less than 0.05 considered significant. Estimates were obtained using a 95% CI. The 3 variable region of the cagA gene was amplified and PCR products of the following sizes corresponded to the following EPIYA motifs: 400 bp: EPIYA AB, 500 bp: EPIYA ABC, 600 bp: EPIYA ABCC and 700 bp: ABCCC. A single PCR band was observed for 58 out of 85 Helicobacter pylori isolates, with an EPIYA distribution motif as follows: 7/85 AB (8.2%), 34/85 ABC (40%), 26/85 ABCC (30.6%) and 18/85 ABCCC (21.2%). However, in 27 out of 85 Helicobacter pylori isolates, two or more bands were observed, where the most predominant cagA genotype were ABC-ABCC (26%, 7/27) and ABCC-ABCCC (22.2%, 6/27). A direct proportionality between the number of EPIYA-C repeats and an increase in the patients' age was observed, finding a greater number of EPIYA ABCC and ABCCC repeats in the population over 50 years old. All isolates were of the Western cagA type and 51.8% of them were found to have multiple EPIYA-C repeats. These standardized molecular test allowed to identify the number of EPIYA C motifs based on band size. © 2020 Rodriguez Gomez et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.